Forcible Displacement Throughout the Ages : Towards an International Convention for the Prevention and Punishment of the Crime of Forcible Displacement. - Dawson, Grant (International humanitarian law series., 2012)
This book analyses the anthropological, historical, and legal contours of the crime of forcible displacement and proposes specific measures that the international community can adopt in order to prevent and/or punish the perpetration of the crime in the future.